Identifikasi Sumber Pertumbuhan Output Nasional: Pendekatan Analisis Input-Output - Nizwar Syafa'at; Sudi Mardianto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2002)
EnglishDuring the economic crisis national output has been contracted, in which actual national production capacity has been decreased because producers were lack of capital and aggregate demand was also decreasing. To speed up the national production recovery, the government needs to implement investment policy on leading national economic sector. Therefore, it is necessary to identify the source of growth of national output, and then identify the leading sector as a direction for investment. This study applied Input-Output analysis approach by using Input-Output Table published by Statistics Indonesia. The results of analysis showed that the source of growth of national output was on agricultural sector, but the problem is lack of the capability of agricultural sector in providing labor and limited income for farmers because land resources which are occupied by the farmers are also limited. To solve this problem, the development of agricultural sector should be integrated with the development of its complement sector. In other words, the development of agricultural sector should be put in the network of agribusiness system development so that agricultural sector is able to be a leading sector in our national economy.IndonesianSelama masa krisis ekonomi, output nasional mengalami kontraksi, dimana kapasitas aktual produksi nasional menurun karena produsen kekurangan modal, disamping permintaan agregat juga turun. Untuk mempercepat pemulihan kapasitas produksi nasional, maka pemerintah perlu menerapkan kebijakan investasi pada sektor andalan ekonomi nasional. Untuk itu, perlu dilakukan identifikasi sumber pertumbuhan output nasional, untuk selanjutnya ditentukan sektor andalan sebagai arahan investasi. Penelitian ini menggunakan pendekatan analisis input-output dengan menggunakan Tabel Input-Output yang diterbitkan oleh Badan Pusat Statistik. Hasil analisis menunjukkan bahwa sumber pertumbuhan output nasional terletak pada sektor pertanian. Namun persoalannya adalah terbatasnya kemampuan sektor pertanian dalam penyediaan tenaga kerja dan pendapatan petani yang sangat terbatas karena sumberdaya lahan yang dikuasai petani juga terbatas. Untuk mengatasi masalah tersebut, maka pengembangan sektor pertanian perlu diintegrasikan dengan pengembangan sektor komplemennya. Dengan kata lain, pengembangan sektor pertanian harus diletakkan dalam kerangka pengembangan sistem agribisnis, sehingga sektor pertanian mampu menjadi sektor andalan ekonomi nasional.